2018
DOI: 10.1016/j.acap.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Care Coordination and Comprehensive Electronic Health Records are Associated With Increased Transition Planning Activities

Abstract: Only 1 in 5 pediatricians have a transition coordinator in their practice and just 15% have a CEHR, even as these resources are associated with improved transition processes for YSHCN. Policy decisions should be made to help practices with supports, such as care coordination and electronic health record implementation, to improve transitions to adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…134 Care coordination is a common feature associated with increased transition planning activities. 135 136 clinicians should incorporate oneon-one time with youth during the medical visit to better prepare youth for managing their own health and health care. One-on-one time has been shown to increase adherence to care, engagement in care, and the likelihood of sharing health risks with their clinician.…”
Section: Outcome Evidence For Pediatric To Adult Hct Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…134 Care coordination is a common feature associated with increased transition planning activities. 135 136 clinicians should incorporate oneon-one time with youth during the medical visit to better prepare youth for managing their own health and health care. One-on-one time has been shown to increase adherence to care, engagement in care, and the likelihood of sharing health risks with their clinician.…”
Section: Outcome Evidence For Pediatric To Adult Hct Interventionmentioning
confidence: 99%
“…159 In the ideal situation, the availability of care coordination support to guide the transition process and team-based care 160 in both the pediatric and adult settings increases chances of success. 135,161 Clinicians from nursing and social work professions often fill this important role and often drive the HCT QI process. 162 -164 Families also need assistance with their new role in the health care of their young adult.…”
Section: Figurementioning
confidence: 99%
“…Receiving family-centered care, care coordination support, care in a medical home, and having a written plan were each positively associated with 2 of the 3 elements (active work to gain skills or understand changes in health at 18 and time alone with an HCP). 47 or between ages 18 and 20. 48 For YSHCN, the finding that care coordination was significantly associated with overall transition performance is also not unexpected.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have shown that care coordination is associated with improved transition procedures, and when pediatric practices have a designated individual responsible for care coordination, they are more likely to have a written transition plan. 47 Current measures of transition planning may not adequately predict youth engagement in care or successful transfer to adult care. 49 With our study, we found that non-Hispanic black or African American youth were more likely to work with their HCP to gain skills and understand changes at 18, compared with non-Hispanic white youth but were also less likely to discuss the shift to an adult HCP.…”
Section: Resultsmentioning
confidence: 99%
“… 21 In addition to the medical summary, having a formal, written transition plan is considered a best practice, 37 and using the electronic health record system is thought to facilitate this task. 104 …”
Section: Transferring the Patient: Best Practices For Paediatric And mentioning
confidence: 99%